Revitalisasi Taman Tanaman Obat Keluarga Di Kampung Jamu: Upaya Peningkatan Kesehatan dan Pelestarian Budaya Lokal Di Kelurahan Kedurus, Surabaya - Putri Nur Pradani, Siska; Argya Darma Herdiyanto, Rafi; Rachmawati, Farikha (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia, 2025)
This community service activity aims to revitalize the Family Medicinal Plant Garden (TOGA) in Kampung Jamu, RW 01, Kedurus Subdistrict, Karang Pilang District, Surabaya City, as a medium for education, cultural preservation, and community empowerment. The revitalization was carried out through a participatory qualitative approach, in which the local community was actively involved in all stages of the activity from planning and implementation to evaluation. This initiative was motivated by the neglected condition of the TOGA garden, the lack of accessible information about the benefits of medicinal plants, and the low level of community involvement in its management. The methods used included field observation, semi-structured interviews with local micro and small business (UMKM) actors, and Focus Group Discussions (FGDs) with residents on July 2, 3, and 5, 2025. The observation activities aimed to identify the current condition of the garden and assess its development potential. The interviews explored the types of plants used, their benefits, and challenges faced by residents. Meanwhile, the FGDs focused on determining plant arrangement patterns, assigning community roles, and formulating a revitalization strategy based on mutual cooperation (gotong royong). One key innovation resulting from this activity was the implementation of QR Codes on plant name boards, allowing visitors to access information about the medicinal benefits of each plant directly on-site. The outcomes of this community service include increased community engagement in garden management, improved physical conditions of the garden, and the expansion of its role as an environmental education tool. The use of QR Codes proved effective as both an educational medium and a way to introduce the benefits of TOGA to the wider community, especially the younger generation. Furthermore, the activity succeeded in strengthening the spirit of mutual cooperation, raising public awareness of the importance of preserving medicinal plants based on local wisdom, and providing a model for empowerment-based revitalization.